2017
DOI: 10.5194/hess-21-651-2017
|View full text |Cite
|
Sign up to set email alerts
|

The canopy interception–landslide initiation conundrum: insight from a tropical secondary forest in northern Thailand

Abstract: Abstract. The interception and smoothing effect of forest canopies on pulses of incident rainfall and its delivery to the soil has been suggested as a factor in moderating peak pore water pressure in soil mantles, thus reducing the risk of shallow landslides. Here we provide 3 years of rainfall and throughfall data in a tropical secondary dipterocarp forest characterized by few large trees in northern Thailand, along with selected soil moisture dynamics, to address this issue. Throughfall was an estimated 88 %… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 80 publications
0
12
0
1
Order By: Relevance
“…At the hillslope scale, the hydrological effects of vegetation are assumed to play a small role on slope stability compared to the contribution of root reinforcement (Sidle and Bogaard, 2016;Sidle and Ziegler, 2017). At the catchment scale, however, the regulation of water fluxes may have important implications for the stability of those slopes that drain large areas, particularly for short and intense rainfall events.…”
Section: Background and Motivationmentioning
confidence: 99%
“…At the hillslope scale, the hydrological effects of vegetation are assumed to play a small role on slope stability compared to the contribution of root reinforcement (Sidle and Bogaard, 2016;Sidle and Ziegler, 2017). At the catchment scale, however, the regulation of water fluxes may have important implications for the stability of those slopes that drain large areas, particularly for short and intense rainfall events.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Tree root systems provide mechanical stability even after forest removal but their reinforcement potential decrease after time, leading to a minimum of potential stabilisation between 3 and 8 years (O'Loughlin, 1974;Sidle et al, 1985;Sidle 1992). At the hillslope scale, hydrological effects are presumably rather inferior compared to the biomechanical effects (Sidle and Ziegler, 2017;Cohen and Schwarz, 2017). From a spatial perspective, the effects of forest cover are strongly dependent on the scale on which slope stability is assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Our observations clearly suggest that the differences observed in hydrological reinforcing effects between grass and hardwood tree covers are negligible, as potentially unstable conditions can be observed at a depth of 100 cm under both vegetation covers, with the F S values less than 1.0 for some dates, therefore supporting the findings of those numerical modelling studies (Chirico et al, ; Arnone et al, ), that differences in hydrological reinforcing effects from different vegetation covers are less evident during wet period. Another study on the interception and smoothing effect of tropical forest canopies showed that the effect was not great enough to mitigate the shallow slope failure initiation for monsoon rainfall conditions (Sidle & Ziegler, ). On the other hand, it was interestingly discovered that the additional hydrological reinforcing effects (2.7 and 2.8 kPa) as a result of induced matric suctions from softwood tree cover (compared with the hardwood tree and grass covers, respectively) contributed to an increase of 0.35 (49.2%) and 0.33 (45.2%) in F S values from 0.71 under hardwood tree cover and 0.73 under grass cover to a value of 1.06 under softwood tree cover during the wettest period.…”
Section: Discussionmentioning
confidence: 99%